(untitled) (Palíndromo, 2021)
Our inaugural critical relationship with the installation points out the way the allegory is yet functioning as a vector of meaning. Conscious of the survival of traditional categories, we try to understand the metamorphic play of what is permanent in history, betting on the power of art to intersect the past and the present times. In opposition to the dogma that considers the new as the driving force of art, we assert that its “ends” rarely breaks with some of the originary motivations we find in ancient theory of art: diverse and transtemporary “ends”, such as the manifestation of an idea, the getting on living of image, the glorification of the artist, even the desire of its own “ending”. Both historical and theoretical, the play with the “end” is a paradoxical dialectics of death and transfiguration. Those challenging concepts are functioning as productive tensors: Alberti, Vasari, De Chirico, Malevich, Kosuth, Meireles, Kaprow and Vik Muniz represent some of the references which gave rhythm to thirty years of research.